2014
DOI: 10.4103/2141-9248.126606
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of nutritional status and foodstuffs in adolescent girls in Iran

Abstract: Background:The prevalence of obesity and overweight in children and adolescents is increasing world-wide. Obesity in children and adolescents is a major risk factor for diabetes, heart diseases, hypertension, and cancer in adulthood.Aim:The aim of the study was to compare the nutritional status and food-stuffs among high-school girls in Arak, Iran, in matter of body mass index (BMI) and associated factors.Subjects and Methods:A cross-sectional survey of a representative sample of 278 adolescents was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
1
2
1
Order By: Relevance
“…The prevalence of thinness among girls in our study was lower than studies in Northern Ethiopia (58.3 %) [ 12 ] and Bangladesh (26 %) [ 41 ]. On the other hand, our study found higher level of thinness among girls compared to studies in Seychelles (14 %) [ 42 ], Iran (10.1 %) [ 49 ], Turkey (11.1 %) [ 50 ], Qatar (5.8 %) [ 51 ] and China (5.2 %) [ 43 ].…”
Section: Discussioncontrasting
confidence: 73%
“…The prevalence of thinness among girls in our study was lower than studies in Northern Ethiopia (58.3 %) [ 12 ] and Bangladesh (26 %) [ 41 ]. On the other hand, our study found higher level of thinness among girls compared to studies in Seychelles (14 %) [ 42 ], Iran (10.1 %) [ 49 ], Turkey (11.1 %) [ 50 ], Qatar (5.8 %) [ 51 ] and China (5.2 %) [ 43 ].…”
Section: Discussioncontrasting
confidence: 73%
“…According to the study's results, school-aged teenage girls made up 9.6% (95% CI: 7.2–11.8) of the population. It was in line with studies conducted in Ethiopia (8.82%), 27 Iran (10.1%), 30 and Ghana (10%). 31 Nevertheless, it was higher than the research reported in Indonesia (5.0%) 22 and Ethiopia (1.4%).…”
Section: Discussionsupporting
confidence: 91%
“…Studies showed that differences in socioeconomic status, differences in individual, environmental, access to health care, beliefs and lifestyles are related to obesity/overweight [14][15][16] .…”
Section: Discussionmentioning
confidence: 99%
“…However, high prevalence of junk food consumption and low health literacy in health workers and families and differences in lifestyle among girls compared to other age-sex groups could cause a normal BMI rather than a high BMJ. 14,20 . Results of other studies showed that fast food intake is associated with high salt and high caloric intake, fat and food poverty 15,21 .…”
Section: Discussionmentioning
confidence: 99%